STUDENTS’ RECOGNITION IN THE DIFFERENCES OF CONTEXTUAL CONTENT WORDS - J Sutomo (Universitas Stikubank (UNISBANK) Semarang, 2012)
This study focuses on the analysis of students’ recognition in the differences of contextual content words: nouns, verbs, adjectives, and adverbs, which data are taken from the work of the second semester students of the FBIB (the Faculty of Language and Cultural Studies) of Unisbank Semarang, in the academic year 2010/2011. The mothodology used in this study is a descriptive, it concerns with how what is or what exists is related to some proceedings that have influenced or affected the present condition or event. The findings showed that the students’ recognition in the differences of contextual content words was not sophisticated. The average number of students who could recognize he content words correctly was 58.42%, and the content word which was mostly recognized incorrectly by he students was the VERB, only 43.85%. Key words: content words, recognition, nouns, verbs, adjectives, adverbs